2012
DOI: 10.1186/1471-2202-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band quantitative and multivariate electroencephalogram analysis of peri-adolescent period

Abstract: BackgroundThe peri-adolescent period is a crucial developmental moment of transition from childhood to emergent adulthood. The present report analyses the differences in Power Spectrum (PS) of the Electroencephalogram (EEG) between late childhood (24 children between 8 and 13 years old) and young adulthood (24 young adults between 18 and 23 years old).ResultsThe narrow band analysis of the Electroencephalogram was computed in the frequency range of 0–20 Hz. The analysis of mean and variance suggested that six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
(139 reference statements)
3
14
0
Order By: Relevance
“…Similar developmental differences were found in periadolescent rats as compared to adult rats in all frequency ranges and both electrode sites (FCTX, PCTX) except for beta frequencies in the frontal cortex. It has long been known that EEG recordings from children are dominated by high amplitude slower rhythms that diminish in amplitude and increase in frequency over the course of adolescence (see [108-112]) and that deviations from normal patterns have been associated with abnormal or delayed brain maturation [113]. It has also been suggested that gray matter loss or synaptic pruning may underlie these developmental changes seen in EEG amplitude over adolescent development [114].…”
Section: Discussionmentioning
confidence: 99%
“…Similar developmental differences were found in periadolescent rats as compared to adult rats in all frequency ranges and both electrode sites (FCTX, PCTX) except for beta frequencies in the frontal cortex. It has long been known that EEG recordings from children are dominated by high amplitude slower rhythms that diminish in amplitude and increase in frequency over the course of adolescence (see [108-112]) and that deviations from normal patterns have been associated with abnormal or delayed brain maturation [113]. It has also been suggested that gray matter loss or synaptic pruning may underlie these developmental changes seen in EEG amplitude over adolescent development [114].…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in brain rhythm frequency might not be exclusively restricted to these rhythms, and other rhythms, such as delta, beta and gamma, could also increase their frequency with age. This possibility is also suggested by the Principal Component Analysis (PCA) of SP in a limited sample of preadolescents and young adults, where the loading components representing the variance related to rhythms from theta to beta showed a slight shift to higher frequencies from preadolescents to young adults (Rodríguez-Martínez et al 2012).…”
Section: Introductionmentioning
confidence: 88%
“…The decrease in absolute spectral power in all frequency bands has been widely found to be one of the landmarks during EEG child development, and it is fulfilled at all the frequencies investigated for the absolute SP (Matousek and Petersén 1973;Gasser et al 1988;Cragg et al 2011;Lüchinger et al 2011;Rodríguez-Martínez et al 2012). The most common hypothesis proposed to explain the decrease in the absolute SP during development refers to the reduction in gray matter associated with maturation (Whitford et al 2007;Feinberg and Campbell 2010;Shaw et al 2006Shaw et al , 2008.…”
Section: Introductionmentioning
confidence: 97%
“…Studies with typical populations using EEG suggest a posterior–anterior developmental progression (Rodríguez Martinez et al., ). At the same time, children's social attention has been shown to be coupled with suppression of the power over the precentral scalp regions and posterior theta power increases (Orekhova, Stroganova, Posikera, & Elam, ).…”
Section: Introductionmentioning
confidence: 99%